2008
DOI: 10.1093/ije/dyn018
|View full text |Cite
|
Sign up to set email alerts
|

The non-cancer mortality experience of male workers at British Nuclear Fuels plc, 1946–2005

Abstract: Background Recent studies of the Hiroshima and Nagasaki A-bomb survivors, together with some (but not all) cohorts exposed occupationally or medically to ionizing radiation, have found an increasing trend in mortality from non-malignant disease with increasing radiation dose. The aim of this study was to establish whether such a trend could be found in a large cohort of employees in the UK nuclear industry.Methods The cohort comprised 64 937 individuals ever employed at the study sites between 1946 and 2002, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
123
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 68 publications
9
123
5
1
Order By: Relevance
“…A statistically significant association, with ERR/Sv of 0.65 (90% CI: 0.36, 0.98), has recently been reported in a large cohort of workers at the British Nuclear Fuels [23]. However, the authors concluded that their results were not consistent with a simple causal interpretation and that further studies were required, including investigation of the possible role of the factors associated with the socio-economic status.…”
Section: Resultsmentioning
confidence: 91%
“…A statistically significant association, with ERR/Sv of 0.65 (90% CI: 0.36, 0.98), has recently been reported in a large cohort of workers at the British Nuclear Fuels [23]. However, the authors concluded that their results were not consistent with a simple causal interpretation and that further studies were required, including investigation of the possible role of the factors associated with the socio-economic status.…”
Section: Resultsmentioning
confidence: 91%
“…In recent analyses of the BNFL cohort (an influential component of the UK contribution to the INWORKS cohort), which had additional information on the exact dates of internal exposure, it was notable that the ERR/Sv estimate for internally monitored workers was actually lower than for workers not monitored for internal radiation (40,41). It may also be possible that internal exposures influence the pattern of risks we are observing; recent findings in the Mayak cohort suggest a possible link between IHD, cerebrovascular disease and plutonium exposure (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Nagasaki and Hiroshima fetal exposure to relatively high levels of radiation (120-230 mSv) led to a deterministic risk of mental retardation, although there is little evidence to support a connection for older children (6). There are also analyses of nuclear industry workers that show a link between radiation exposure and cardiovascular disease (41). The potential risk of additional adverse effects from radiation exposure should be noted, but at present there are not enough data to quantify the increased risk, especially for low levels of radiation and for the pediatric population.…”
Section: Dosimetry and Riskmentioning
confidence: 99%